The Effect of Contextual Teaching and Learning Using PhET Media on Higher-Order Thinking Skills in the Energy Material - Marlina, Lisa; Supriadi, Gito; Rizal, Setria Utama (Jurnal Pijar Mipa, 2025)
Natural and Social Sciences (IPAS) learning in schools often faces challenges, especially in improving students’ higher-order thinking skills. One of the factors that results in low learning outcomes in higher-order thinking skills is the use of learning models that do not involve students fully and actively. Therefore, an innovative and effective learning model is needed, one of which is the contextual teaching learning model using PhET media. This study was conducted to examine the application of the Contextual Teaching and Learning (CTL) model using PhET media on energy materials in grade 4 elementary school, and the significant influence of the Contextual Teaching and Learning (CTL) model using PhET media on Higher Order Thinking Skills in energy materials in grade 4 elementary school. he method used is a quasi-experimental qualitative design with a one-group pretest-posttest design. Data in the study were obtained through observation, tests and documentation. The data analysis technique in this study uses observation sheets to see the application of the contextual teaching learning model using PhET media, with a score of 87.5 in the satisfactory category. Descriptive statistical data were obtained; the average pretest score was 44.00. Then, after applying the Contextual Teaching and Learning (CTL) learning model using PhET media, it increased to 90.87. The normality test obtained a pre-test value of 0.057 ˃ 0.05, so the distribution of data in this pretest was distributed normally. As for the post-test, the results of higher-order thinking skills have a value of 0.541 ˃ 0.05 with normal distribution. The hypothesis test uses the Wilcoxon Signed Ranks Test with a Mean Rank of 8.00 and a Sum of Rank of 120.00 with a significance value of 0.000, which means that it is less than the significance level (α) of 0.05, so that H₀ is rejected. This means that there is a significant difference between pre-test and post-test scores. In conclusion, the Contextual Teaching and Learning (CTL) learning model using PhET media has an effect on Higher Order Thinking Skills in energy materials in grade 4 elementary school.